Audit committees and COVID-19-related disclosure tone: Evidence from Oman - Badar Alshabibi; Shanmuga Pria; Khaled Hussainey (Journal of Risk and Financial Management, 2021)
In this study, we content analyzed chairman's statements to measure the tone of COVID-19-related disclosure in Omani listed firms for the year ending 2020. We also examined whether audit committee (AC) characteristics influence disclosure tone. After controlling for corporate board and firm characteristics, our regression analysis showed that two AC characteristics (gender diversity and overlapped directors) positively affect good news information and negatively affect bad news information. It also showed that AC size positively affects bad news information. No evidence was found that the AC independence, meeting frequency, multi-directorships, and financial expertise have an impact on the tone of COVID-19-related disclosures. Our paper contributes to the growing literature by being the first study to examine whether AC characteristics influenced disclosure tone during the COVID-19 pandemic. Our results indicate that investors and regulatory bodies should take AC characteristics into account in determining the tone of COVID-19-related disclosures.
Keywords: 330; COVID-19-related disclosure tone; audit committee; chairman’ s statement; Sultanate of Oman